Complementary crosstalk between palmitoylation and phosphorylation events in MTIP regulates its role during Plasmodium falciparum invasion - Anam, Zille; Kumari, Geeta; Mukherjee, Soumyadeep; Rex, Devasahayam Arokia Balaya; Biswas, Shreeja; Maurya, Preeti; Ravikumar, Susendaran; Gupta, Nutan; Kushawaha, Akhilesh Kumar; Sah, Raj Kumar; Chaurasiya, Ayushi; Singhal, Jhalak; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Post-translational modifications (PTMs) including phosphorylation and palmitoylation have emerged as crucial biomolecular events that govern many cellular processes including functioning of motility- and invasion-associated proteins during Plasmodium falciparum invasion. However, no study has ever focused on understanding the possibility of a crosstalk between these two molecular events and its direct impact on preinvasion- and invasion-associated protein–protein interaction (PPI) network-based molecular machinery. Here, we used an integrated in silico analysis to enrich two different catalogues of proteins: (i) the first group defines the cumulative pool of phosphorylated and palmitoylated proteins, and (ii) the second group represents a common set of proteins predicted to have both phosphorylation and palmitoylation. Subsequent PPI analysis identified an important protein cluster comprising myosin A tail interacting protein (MTIP) as one of the hub proteins of the glideosome motor complex in P. falciparum, predicted to have dual modification with the possibility of a crosstalk between the same. Our findings suggested that blocking palmitoylation led to reduced phosphorylation and blocking phosphorylation led to abrogated palmitoylation of MTIP. As a result of the crosstalk between these biomolecular events, MTIP’s interaction with myosin A was found to be abrogated. Next, the crosstalk between phosphorylation and palmitoylation was confirmed at a global proteome level by click chemistry and the phenotypic effect of this crosstalk was observed via synergistic inhibition in P. falciparum invasion using checkerboard assay and isobologram method. Overall, our findings revealed, for the first time, an interdependence between two PTM types, their possible crosstalk, and its direct impact on MTIP-mediated invasion via glideosome assembly protein myosin A in P. falciparum. These insights can be exploited for futuristic drug discovery platforms targeting parasite molecular machinery for developing novel antimalarial therapeutics.